(untitled) (LACCEI, 2024)
The location and capacity of charging stations influence the growth of the electric vehicle industry, since they offer users adequate station locations that consider the shortest distance traveled and maximum service capacity. For this reason, in this article a comparative analysis of location criteria is carried out through ArcGIS, so that, through its parameters obtained as maximum travel distance, minimum travel distance and load capacity, these data can be compared and determine what is the optimal criteria to use. Likewise, a case study is developed in a city with an area of 9.62 km to validate that the chosen criterion is the most appropriate for an optimal location of charging stations for electric vehicles. Finally, when the analysis and interpretation of the results obtained is carried out, it is determined that the maximum capacitated coverage criterion is adequate for an optimal location of charging stations since it presents a minimum travel time, waiting time and recharging time in comparison with other criteria.